Corporate social responsibility in the mining sector in South Africa : the impact on financial perfomance - Nemaranzhe, Thakhani (My University, 2019)
Corporate Social Responsibility (CSR) remains a much-debated topic in the business world as more companies are increasingly acknowledging the need for CSR in one way or another. However, the debate on whether CSR benefits a company financial remains. Researcher’s effort to analyse the value of CSR on company’s financial performance has revealed inconclusive and inconsistent results. In South Africa, CSR in the mining sector is seen as an important tool, to alleviate poverty, address inequity and create a safe environment for the community. This study examines the relationship between CSR and Financial Performance of 21 mining companies listed on the Johannesburg Stock Exchange (JSE). CSR is measured using the JSE Social Responsibility Index (SRI), and Financial Performance as measured using Return on Assets (ROA), Tobin’s Q and Market Value Add (MVA). The Arellano and Bond estimator model showed that there is a negative relationship between CSR and ROA, Tobin’q and MVA. Therefore one can conclude that there is no relationship between CSR and financial performance. However, the t-test showed a positive relationship between CSR and ROA. The inconsistency in the results, can therefore render the overall study results as inconclusive
MBA
Keywords: Social responsibility of business -- South Africa. Corporate governance -- South Africa. Banks and banking -- South Africa.